2001
DOI: 10.1021/jp010381i
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Study on Molecular Motions of Benzene Adsorbed in ZSM-5 Zeolite:  Role of Charge-Balancing Cations and Pore Size

Abstract: Occlusion of benzene in NaZSM-5 zeolite is investigated using in situ FTIR spectroscopy as a function of substitution of Na+ with group IIA cations. At least four pairs of overlapping vibrational bands were observed in the region of out-of-plane C−H bending vibrations (2000−1800 cm-1) on adsorption of benzene in NaZSM-5 at room temperature. Whereas two pairs of these bands, e.g., one pair at around 2007 and 1986 cm-1 and the other at 1969 and 1956 cm-1, correspond to the 1960 cm-1 band of liquid benzene, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 23 publications
4
35
0
Order By: Relevance
“…Therefore, it is not unreasonable that this loading is indeed close to the saturation limit. Similar values were found or discussed in previous works [34][35][36][37].…”
Section: Radial Distribution Functionssupporting
confidence: 92%
“…Therefore, it is not unreasonable that this loading is indeed close to the saturation limit. Similar values were found or discussed in previous works [34][35][36][37].…”
Section: Radial Distribution Functionssupporting
confidence: 92%
“…22 This is in agreement with our contention that in their occluded state, the hexagonal plane of benzene molecules is parallel to the walls of MCM pores, causing no direct binding to the internal hydroxy groups. 18 The results of our QENS and IR studies are in line with the process of capillary condensation of fluids in narrow pores. It is well reported that the average density of the capillary gas is usually larger than that of the bulk gas.…”
Section: Discussionsupporting
confidence: 81%
“…Further, the width of this band is found to be ∼12.7 cm -1 in the case of NaZSM-5, which is in conformity with the reported behavior of benzene molecules in the pores of ZSM-5 zeolites. 18,19 5. As discussed in our earlier publications, the increase in intensity ratio of the fundamental vibration (ν 19 ) at 1479 cm -1 and the other in-plane vibrations at 3092, 3071, and 3039 cm -1 is a feature associated with the transformation of benzene to a more condensed state.…”
Section: Discussionmentioning
confidence: 99%
“…Figure b shows the FTIR spectra of heat‐treated polymer at 969 V. This spectrum shows characteristic peak at 3650–3730 cm −1 because of absorbed water , and the peak around 2150 and 2000 cm −1 for the strong ketene carbonyl stretch absorption band of Dioxine or C–H out of plane bending vibrations band for benzene or ethylene . Another peaks around 663 cm −1 may be because of C=C aromatic torsion and deformation or trans unsaturation bending of CH=CH . And rest of the peaks for polyester were removed to indicate that polyester has been removed successfully after heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this comparison, the polymer coated on WCW was found to be polyester. Figure 2b shows the FTIR spectra of heat-treated polymer at 969 V. This spectrum shows characteristic peak at 3650-3730 cm 21 because of absorbed water [20], and the peak around 2150 and 2000 cm 21 for the strong ketene carbonyl stretch absorption band of Dioxine or C-H out of plane bending vibrations band for benzene or ethylene [21,22]. Another peaks around 663 cm 21 may be because of C¼C aromatic torsion and deformation [16,19] or trans unsaturation bending of CH¼CH [24].…”
Section: Ftir Analysis Of Wcw-coated Polymer Before and After Heat Trmentioning
confidence: 99%